Web Application Review of Goods and Services for Reviewer Module - Anranur Uwaisy Marchiningrum; Reza Budiawan; Villy Satria Pradithae; Ario Harry Prayogo (G-Tech: Jurnal Teknologi Terapan, 2026)
Online reviews of goods and services are essential in supporting informed consumer decision-making; however, user participation in review activities in Indonesia remains limited, resulting in fragmented and less credible information. This study aims to design and develop a web-based social application, namely the Reviewing Goods and Services Web Application (RIPIU), focusing on the reviewer module to support structured, interactive, and experience-based reviews. The application was developed using the Software Development Life Cycle (SDLC) with the waterfall model, including needs analysis, system design, implementation, and functional testing. Data collection was conducted through interviews, questionnaires, and comparative analysis of existing review platforms. The results indicate that the reviewer module was successfully implemented with key features such as review creation and management, goods and services search, question-and-answer interaction, profile customization, and a reward mechanism for active reviewers. Black box testing confirms that all system functionalities operate according to specified requirements. This research contributes an applied web-based review system that enhances user engagement and provides comprehensive product and service information, supporting the practical implementation of social-based information systems in the e-commerce domain.